Aportacions a la història del lèxic nord-occidental - Farreny Sistac, Dolors (Caplletra. Revista Internacional de Filologia, 1999)
The author presents the tentative results of a lexical research carried out on a collection of seven criminal prosecutions between 1482 and 1598 preserved in the Arxiu Municipal de la Pacria in Lleida. A fraction of the 33 gleaned words was still unattested in basic lexicographical compilations; in other cases an earlier date for the word has been obtained or information has been implemented with the north-western witness.